Primary Pulmonary Leiomyosarcoma : an Extremely Rare, Difficult-to-Manage Case of Lung Cancer - Ngakan Putu Parsama Putra; Ungky Agus Setyawan; Dini Rachma Erawati; Hendy Setyo Yudhanto; Binharyanto, Adlan Pratama Binharyanto (Malang Respiratory Journal, 2023)
Background: Primary Pulmonary Leiomyosarcoma (PPL) known as <0.5% of total lung cancer. Histopathological examinations are the pillars of PPL diagnosis as clinical manifestations and radiological features are usually not specific. Treatments of PPL include surgical resection, radiotherapy, and chemotherapy. Case Illustration: A 51-year-old male, smoker, with a productive cough for 2 weeks, accompanied by chest pain, weight loss, and loss of appetite. Imaging studies showed a solid mass in the right lung, which was confirmed through bronchoscopy, cytology, histology, and immunohistochemistry evaluations. Bronchoscopy showed an intraluminal mass in the right main bronchus suggesting malignancy. Immunohistochemistry of Desmin and Smooth Muscle Actin, which were positive, confirmed the diagnosis of PPL of the right lung stage T4N1M1a IVA. Discussion: Surgical resection is the gold standard treatment for PPL whose clinical conditions and tumor spread still allowed for safe operation. Surgical resection did not undergo because already in stage IVA. Radiotherapy and chemotherapy can be added for patients who are unable to have surgery. There are no guidelines regarding chemotherapeutic regimens that are recommended for PPL. Cisplatin/carboplatin and etoposide are two chemotherapeutic agents that are commonly used in other variants of lung cancer. Cisplatin is successful in 5-23% of patients and etoposide is successful in 8%. Doxorubicin and ifosfamide are usually used for soft tissue sarcoma too. After administration of 4 cycles of carboplatin/etoposide, a chest CT scan with contrast recist shows the progression of PPL. Conclusion: Carboplatin and etoposide have been long used as therapy for lung cancer. Currently, available literature shows that their effectiveness in PPL is still considered low. Nevertheless, more studies are needed to further explore the possibilities of using carboplatin and etoposide in PPL patients. Keywords: chemotherapy, lung cancer, primary pulmonary leiomyosarcoma